Biocidal polymers - Pal Singh Chauhan, Narendra (De Gruyter, 2019)
Biocidal polymers are designed to inhibit or kill microorganisms such as bacteria, fungi and protozoans. This book summarizes recent findings in the synthesis, modification and characterization of various antimicrobial polymers ranging from plastics and elastomers to biomimetic and biodegradable polymers. Modifications with different antimicrobial agents as well as antimicrobial testing methods are described in a comprehensive manner- Resumé vydavatel